Awe/Gratitude as an Experiential Aspect of Spirituality and Its Association to Perceived Positive Changes During the COVID-19 Pandemic - Büssing, Arndt; Rodrigues Recchia, Daniela; Dienberg, Thomas; Surzykiewicz, Janusz; Baumann, Klaus (Frontiers in Psychiatry, 2021)
Background: While the COVID-19 pandemic has affected the lives of almost all people worldwide, many observed also positive changes in their attitudes and behaviors. Best predictors of these perceived changes were the experience of wondering Awe, with subsequent feelings of Gratitude. Now we intended to analyze 1) by whom Awe/Gratitude was experiences, 2) how these feelings relate to perceived changes and experienced burden, and 3) whether Awe/Gratitude contribute to participants’ wellbeing or may buffer perceived burden in terms of a resilience factor. Methods: Online survey with standardized questionnaires (i.e., WHO-Five Well-being Index, Awe/Gratitude Scale, Perceived Changes Questionnaire) among 2,573 participants (68% women; mean age 48.7±14.2 years) from Germany recruited between June and November 2020. Results: Awe/Gratitude scored significantly higher among women (Cohen´s d=.40), older persons (d=.88), persons who rely on their faith as a “strong hold in difficult times” (d=.99), with higher wellbeing (d=.70) and lower perceptions of loneliness (d=.49). Regression analyses revealed that best predictors of Awe/Gratitude (R2=.40) were frequency of meditation, female gender, life satisfaction, wellbeing, faith as a strong hold, perceived burden, and life reflection. Best predictors of participants´ wellbeing were life satisfaction and low perceived burden, and further Awe/Gratitude and Nature/Silence/Contemplation, explaining 47% of wellbeing variance. However, Awe/Gratitude cannot be regarded as a buffer of the negative aspects of the COVID-19 pandemic, as it is only marginally (though negatively) related to perceived burden (r=-.15). Mediation analysis showed that Awe/Gratitude mediates 42% of the link between wellbeing as a predictor on Nature/Silence/Contemplation as an outcome and has a direct effect of β=0.15 and an indirect effect of β=0.11. Further, Awe/Gratitude mediates 38% of the link between Nature/Silence/Contemplation as a predictor on wellbeing as the outcome; the direct effect is β=0.18 and the indirect effect is β=0.11. Conclusions: The general ability to experience Awe/Gratitude during the COVID-19 pandemic may sensitize to perceive the world around more intensely, probably in terms of posttraumatic growth. However, this experience of Awe/Gratitude does not necessarily buffer against adverse events in life and cannot prevent perceived burden, but it facilitates to nevertheless perceive positive aspects of life even within difficult times.